NoobLab: An Intelligent Learning Environment for Teaching Programming - Neve, Paul; Hunter, Gordon; Livingston, David; Orwell, James (2012 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2012)
Computer programming is a highly practical subject and it is essential that those new to the discipline engage in hands-on experimentation as part of the learning process. However, when faced with large cohorts and an increasing demand for distance and student flexible learning, incorporating this into a programming course can be difficult. There is a dynamic that exists between tutor and student in a real-world programming workshop session that is not easily replicated online. In this paper we describe an online learning environment that begins to create an analogue of this dynamic and its successful integration into an undergraduate programming module. Ultimately, the potential exists to not only improve the student learning experience but also investigate and inform programming pedagogy itself.